2020
DOI: 10.1088/1742-6596/1657/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Problem solving and cognitive style: An error analysis

Abstract: Problem-solving and cognitive style are two things that are important to note, but the reality is rarely considered especially cognitive style. Student cognitive style can influence problem-solving abilities. This study aims to investigate student errors based on Newman in problem solving, in terms of independent and dependent field cognitive style. The study was conducted on junior high school students in Indonesia, the method used is exploratory involving 2 Subject. Subjects are taken from independent and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It was found that students still experienced many difficulties when learning linear algebra, especially in the matter of systems of linear equations (SPL) using the Gauss-Jordan method. (Ramadhani, 2017;Pradiarti & Subanji, 2022). In addition, students also experience difficulties in concluding the correct solution, especially in SPL, which has many answers, and SPL which does not have a solution (Vitantri, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that students still experienced many difficulties when learning linear algebra, especially in the matter of systems of linear equations (SPL) using the Gauss-Jordan method. (Ramadhani, 2017;Pradiarti & Subanji, 2022). In addition, students also experience difficulties in concluding the correct solution, especially in SPL, which has many answers, and SPL which does not have a solution (Vitantri, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The difficulties experienced by students can result in errors in solving problems [7]. Students made mistakes in transforming mathematical models, doing the counting process, making wrong conclusions, and not being able to determine the settlement strategy and were wrong in compiling a mathematical model regarding the related material in the study [8][9]. It is a condition that deserves further attention.…”
Section: Introductionmentioning
confidence: 99%